2022
DOI: 10.3390/pathogens11060705
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Serotypes, and Antimicrobial Resistance Patterns of Non-Typhoid Salmonella in Food in Northern Taiwan

Abstract: Salmonella is one of the most common bacteria causing food poisoning worldwide. We evaluated the prevalence, the serotypes, and the antimicrobial resistance (AMR) of Salmonella isolates from many kinds of food, particularly pork and chicken in retail, in Taiwan between January 2017 and December 2019. The E-test was used to assess antimicrobial susceptibility and a polymerase chain reaction was performed for serotyping. A total of 459 different foods were investigated, and 117 Salmonella strains were isolated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
6
0
2
Order By: Relevance
“…A single S. Brancaster isolate was obtained from migratory birds. This serovar has been associated with human infection in Nigeria ( Ifeanyi et al, 2014 ) and Senegal ( Cardinale et al, 2005 ), and detected in poultry meat in Singapore, Malaysia, and Taiwan ( Chin et al, 2017 ; Zwe et al, 2020 ; Chang et al, 2022 ). Multidrug resistance is common and associated with a core set of AMR genes, which were present in the wild bird isolates, comprising floR (phenicol), qnrS (quinolone), bla TEM-176 (ampicillin), tet (A; tetracycline), dfrA14 (trimethoprim), and aph ( 3′ ) -Ia (aminoglycosides; Chin et al, 2017 , Zwe et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A single S. Brancaster isolate was obtained from migratory birds. This serovar has been associated with human infection in Nigeria ( Ifeanyi et al, 2014 ) and Senegal ( Cardinale et al, 2005 ), and detected in poultry meat in Singapore, Malaysia, and Taiwan ( Chin et al, 2017 ; Zwe et al, 2020 ; Chang et al, 2022 ). Multidrug resistance is common and associated with a core set of AMR genes, which were present in the wild bird isolates, comprising floR (phenicol), qnrS (quinolone), bla TEM-176 (ampicillin), tet (A; tetracycline), dfrA14 (trimethoprim), and aph ( 3′ ) -Ia (aminoglycosides; Chin et al, 2017 , Zwe et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella , a foodborne pathogen, causes gastroenteritis with severity ranging from diarrheal symptoms to death ( Bae et al, 2013 ). Salmonella is one of the most common pathogens causing foodborne poisoning and is listed as a significant cause of illness and death by the World Health Organization ( Chang et al, 2022 ). To date, approximately 2,600 serotypes have been identified and the majority of them can cause cross-infection between animals and humans ( Raufu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For several decades, Salmonella Pullorum and S. Enteritidis are typically the most common serovars with economic impact responsible for Salmonella infection in poultry and humans. However, this predominance has decreased in many regions of the world, where other examples of NTS, such as Salmonella Infantis, Salmonella Derby, and Salmonella Anatum, have become the dominant serovars, reflecting the current situation in many countries [ 8 23 ]. The S. Brancaster in this study were all isolated from healthy chicken flocks with no reported clinical disease or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance to ciprofloxacin, a critically important antimicrobial in treating Salmonella infection or typhoid fever in humans, was at 9%, i.e., much higher than those reported by others ranging from 0%–3.8% [ 16 ]. Invasive infections caused by ciprofloxacin-resistant Salmonella have been reported to cause pneumonia, gastroenteritis, fever, septic arthritis, and meningitis in children or immunocompromised adults [ 8 ]. MDR Salmonella has been reported to be more virulent and cause a direct threat to human health when treatment is hampered by resistance [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation